Antimicrobial resistance in wastewater of Yangon Region, Myanmar from one health perspective - Thandar, Mya; Win, Hla Hla; Oo, Khin May; Kyi, Moh Moh; Khine, Myat Su (International Journal Of Community Medicine And Public Health, 2021)
Background: Antibiotic resistance is an emerging concern both for public and animal health globally and also threatens the achievements of modern medicine. This study aimed to generate the baseline data of drug resistance pathogens in diversity of waste water of Yangon Region, Myanmar. Methods: A cross-sectional descriptive study was conducted from January to July 2021. A total of forty samples of wastewater (two samples each from ten hospitals, one sample each from five poultry farms, five aquacultures and ten community drains) were aseptically collected, transported in ice box and processed following standard procedure for bacterial isolation and detection of antibiotic sensitivity pattern. Identification and antibiotic susceptibility testing of isolated colonies were done by VITEK 2 compact system. Results: A total of 106 bacterial isolates were identified and 50% were from hospitals, 31.1%were from community drains and 9.4% each from poultry farms and aquacultures. The most frequently identified isolates were Enterobacteriaceae (65.1%) followed by Acinetobacter species (11.3%) and Pseudomonas species (8.5%). Among the isolated organisms, ESBL producers and Carbapenemase producer were 7.5% and 0.9% respectively. ESBL producers (62.5%) were resistant to cefuroxime, cefuroxime-axetil, cefotaxime, ceftriaxone and minocycline. Carbapenem resistant Enterobacteriaceae was multidrug resistant but sensitive to amikacin, tigecycline and cefaclor. Conclusions: The proportion of antibiotic resistant bacteria are higher in hospital wastewater than other sites. Hence proper treatment plant for hospital wastewater should be installed and need to mitigate antibiotic resistance with a ‘one-health’ approach.